Analisis Peran Komunikasi dalam Resolusi Konflik Kelompok Mahasiswa di Universitas Islam Negeri Sumatera Utara - Wasiyem Wasiyem; Tari Uswatun Nisa Siregar; Dinda Mutiara; Shinta Aulia Agusta; Dwi Ulan Dari; Devi Helma Fitri Hasibuan; Dwi Rizky Sidabalok (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Conflict is a common dynamic within student groups, often arising from differences in background, perspectives, and communication styles. This study aims to analyze the role of communication in resolving group conflicts among students at the State Islamic University of North Sumatra. Using a descriptive quantitative approach, 36 active students with group work experience were selected as respondents through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed descriptively. The results indicate that comfort in expressing opinions (61.1%) and willingness to listen (72.2%) are key indicators of effective communication. Nevertheless, 69.4% of respondents reported experiencing conflicts, mostly due to misunderstandings and ineffective communication (77.8%). Open communication, group discussions, and the active role of group leaders were found to significantly facilitate conflict resolution. However, satisfaction with conflict resolution was relatively low, with only 55.6% expressing satisfaction, indicating a need to enhance interpersonal communication skills and leadership roles. This study recommends strengthening a culture of open, honest, and participatory communication as a key to fostering harmonious and productive student group dynamics.